Computer Training in Fostering a Digital Literacy Culture of PKK Cadres Tejorejo Village - Muhammad Ilham Akbar; Citra Anisatun Nabila; Siti Zulaikhah; Selvi Kurnia; Muhammad Alfandhi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The aim of this computer training is to provide introduction and computer training to the Tejorejo village community, especially PKK cadres. Participants in this training are PKK cadre mothers aged 30-50 years. This training activity is a work program from the KKN MIT-18 Posko 49 UIN Walisongo Semarang activities for the Tejorejo village community. Through this activity, training participants can know and understand computers, especially Microsoft Office, to help with school assignments and other tasks in their daily activities. The result of this training is that students better understand the role of computers and the use of Microsoft Office and are motivated to complete tasks using computers